Sue Westwood (ed.) (2019). Ageing, Diversity and Equality: Social Justice Perspectives. Abingdon and New York: Routledge, 376 pp. ISBN: 978-0-415-78669-0 (hardback) - Rosita Dissels; Ada Lui Gallassi (International Journal of Ageing and Later Life, 2019)
This edited collection brings a comprehensive insight into inequality and diversity of ageing, exploring the concept of social justice in gender; sexualities; culture, ethnicity and religion; disabilities, long-term conditions and care; and spatiality. The understanding of ageing diversity in social gerontology scholarship is underdeveloped and information about minority groups in the older population is often placed in retrofitted sections. Therefore, the aim of this book is to make an important contribution to fill this gap. It consists of five parts, in which inequalities associated with ageing and diversity are centred within Nancy Fraser’s theory of social justice (2013). In Chapter 1, Sue Westwood, the editor of this volume, introduces the book and presents a deeper notion of the concept of intersectionality in the field of socio-gerontology. She recognizes the importance to employ this concept, which refers to intertwined inequality in people’s experiences of disadvantage and discrimination, in order to understand the heterogeneity and diversity of ageing, enabling to clarify the complexity of inequality in old age.